2020
DOI: 10.1002/pro.3936
|View full text |Cite
|
Sign up to set email alerts
|

Comparing the binding properties of peptides mimicking the Envelope protein of SARS‐CoV and SARS‐CoV‐2 to the PDZ domain of the tight junction‐associated PALS1 protein

Abstract: The Envelope protein (E) is one of the four structural proteins encoded by the genome of SARS-CoV and SARS-CoV-2 Coronaviruses. It is an integral membrane protein, highly expressed in the host cell, which is known to have an important role in Coronaviruses maturation, assembly and virulence. The E protein presents a PDZ-binding motif at its C-terminus. One of the key interactors of the E protein in the intracellular environment is the PDZ containing protein PALS1. This interaction is known to play a key role i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
49
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 50 publications
(54 citation statements)
references
References 18 publications
4
49
1
Order By: Relevance
“…1 , Supplementary Data 1 ). It is to be noted here, aa variations in this domain, particularly Ser 55 -Phe 56 and Arg 69 predicted to improve the interaction of SARS-CoV-2 Envelope protein to tight junction-associated PALS1 than SARS-CoV ( De Maio et al, 2020 ; Toto et al, 2020 ). Furthermore, aa at C-terminal end (DLLV: 72–75) directly interact with the PALS1 protein.…”
Section: The Studymentioning
confidence: 61%
See 2 more Smart Citations
“…1 , Supplementary Data 1 ). It is to be noted here, aa variations in this domain, particularly Ser 55 -Phe 56 and Arg 69 predicted to improve the interaction of SARS-CoV-2 Envelope protein to tight junction-associated PALS1 than SARS-CoV ( De Maio et al, 2020 ; Toto et al, 2020 ). Furthermore, aa at C-terminal end (DLLV: 72–75) directly interact with the PALS1 protein.…”
Section: The Studymentioning
confidence: 61%
“…However, C-terminal domain of monomeric E protein affects the host's intracellular activities through interference with the endoplasmic reticulum, Golgi and the ER-Golgi intermediate compartment ( Li et al, 2014 ). Interaction between the C-terminal domain binding motif (DLLV) of SARS Envelope and PALS1 disrupt tight junctions of epithelial cells promoting virus spread and thus play a key role in the SARS-CoV pathology and suspected to affect the integrity of the lung epithelia ( De Maio et al, 2020 ; Toto et al, 2020 ).…”
Section: The Studymentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, the SARS-CoV-1 E protein was shown to interact with the PDZ domain of TJ protein PALS1, resulting in mislocalization of PALS1 and delayed formation of TJs in a renal model. In a subsequent study, the C-terminal sequences of SARS-CoV-2 E protein were also predicted to bind to the PDZ domain of PALS1 [14, 15]. We did not detect an E-PALS1 interaction, since the PDZ domain of PALS1 was not included in the screening array (Fig 2).…”
Section: Discussionmentioning
confidence: 94%
“…Intriguingly, the extreme C-terminal (ECT) sequence of the E protein of SARS-CoV-2 is similar to that of SARS-CoV-1, suggesting that it may also interact with specific host PDZ-domain bearing proteins via this putative PBM. Indeed, recent studies showed that the SARS-CoV-2 E protein exhibited an increased affinity for PALS1 [9, 15].…”
Section: Introductionmentioning
confidence: 99%